Posterior cingulate γ-aminobutyric acid and glutamate/glutamine are reduced in amnestic mild cognitive impairment and are unrelated to amyloid deposition and apolipoprotein E genotype - Riese, Florian; Gietl, Anton; Zölch, Niklaus; Henning, Anke; O’Gorman, Ruth; Kälin, Andrea M.; Leh, Sandra E.; Buck, Alfred; Warnock, Geoffrey; Edden, Richard A.E.; Luechinger, Roger; Hock, Christoph; et al. (Neurobiology of aging, 2015)
The biomarker potential of the inhibitory neurotransmitter γ-aminobutyric acid (GABA) for the in vivo characterization of preclinical stages in Alzheimer's disease has not yet been explored. We measured GABA, glutamate + glutamine (Glx), and N-acetyl-aspartate (NAA) levels by single-voxel MEGA-PRESS magnetic resonance spectroscopy in the posterior cingulate cortex of 21 elderly subjects and 15 patients with amnestic mild cognitive impairment. Participants underwent Pittsburgh Compound B positron emission tomography, apolipoprotein E (APOE) genotyping, and neuropsychological examination. GABA, Glx, and NAA levels were significantly lower in patients. NAA was lower in Pittsburgh Compound B-positive subjects and APOE ε4 allele carriers. GABA, Glx, and NAA levels were positively correlated to CERAD word learning scores. Reductions in GABA, Glx, and NAA levels may serve as metabolic biomarkers for cognitive impairment in amnestic mild cognitive impairment. Because GABA and Glx do not seem to reflect amyloid β deposition or APOE genotype, they are less likely biomarker candidates for preclinical Alzheimer's disease.